CLAY MINERAL COMPOSITION AND PALAEOCLIMATIC INTERPRETATION OF THE PLEISTOCENE DEPOSITS OF UKRAINE - Perederij V.I. (My University, 2001)
The Pleistocene deposits on the plains regions of Ukraine are subaerial and subaqueous formations of diverse types. Loesses and fossil soils represent 16 climatic stages (8 warm and 8 cold) of the Pleistocene and environmental changes are reflected in their clay mineral composition. Clay fractions (< 0.001 mm) of all 16 stages from 34 key sites and boreholes in different regions were analysed mineralogically. In the loesses and palaeosols the main clay minerals are of the smectite group (montmorillonite, nontronite, beidellite), hydromicas, mixed layer hydrumica-montmorillonite minerals. kaolinite and halloysite. Chlorite, goethite, calcite, gypsum. and quartz are also present. There are differences in the amounts of the main minerals in palaeosols and loess horizons of different ages. Regional differences in the clay mineral composition of two Middle Pleistocene stages - the Zavadovka and Dnieper were studied. Changes in mineral composition at 12 key Pleistocene: sites in different regions indicate temporal (rhythmic) and spatial (regional) changes that reflect the palaeoclimatic conditions.
Keywords: Pleistocene; Clay mineral; Ukraine; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен